2009
DOI: 10.1111/j.1365-2966.2009.15201.x
|View full text |Cite
|
Sign up to set email alerts
|

The orientations of molecular clouds in the outer Galaxy: evidence for the scale of the turbulence driver?

Abstract: Supernova (SN) explosions inject a considerable amount of energy into the interstellar medium (ISM) in regions with high-to-moderate star formation rates. In order to assess whether the driving of turbulence by supernovae is also important in the outer Galactic disc, where the star formation rates are lower, we study the spatial distribution of molecular cloud (MC) inclinations with respect to the Galactic plane. The latter contains important information on the nature of the mechanism of energy injection into … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…In the Milky Way, the driving scale can be probed by measuring the correlation scale of molecular clouds with similar inclinations with respect to the Galactic disc. Using this method, Dib et al (2009) estimated a driving scale 100 pc comparable to that found in our simulations. In external galaxies, the driving scale can be estimated by measuring the ISM velocity power spectrum, for example using HI gas observations (e.g.…”
Section: Results Of the Energetics Analysissupporting
confidence: 57%
“…In the Milky Way, the driving scale can be probed by measuring the correlation scale of molecular clouds with similar inclinations with respect to the Galactic disc. Using this method, Dib et al (2009) estimated a driving scale 100 pc comparable to that found in our simulations. In external galaxies, the driving scale can be estimated by measuring the ISM velocity power spectrum, for example using HI gas observations (e.g.…”
Section: Results Of the Energetics Analysissupporting
confidence: 57%
“…Lin & Shu (1964) predict that the influence of spiral-arm shocks is significantly weaker in the outer Galaxy beyond the corotation radius (R GC ∼ 8 kpc). This would lead to less confined and smooth spiral features outside this radius, with supernovae probably playing a more important role than the spiral structure in determining the state of the ISM (Dib et al 2009). Our RMS sources are young enough that they are still embedded in their natal molecular clouds and have not been dispersed by the Galactic gravitational potential, and are thus a good probe of changes in the molecular ISM.…”
Section: Galactic Mid-plane and Scaleheight Distributionsmentioning
confidence: 99%
“…This drop in the metallicity gradients is interpreted by the authors as being due to a gap in the dense gas at the co-rotation radius, with smaller gas flows and consequently fewer mergers producing massive clumps outside the co-rotation radius than inside (see Lumsden et al 2013 for a more detailed discussion). While spiral arms are thought to play an important role in forming dense molecular structures within the co-rotation radius (e.g., Terebey 1998 andDobbs et al 2006) it is likely that this process is regulated by a different mechanism in the outer Galaxy, such as supernovae (Dib et al 2009). Alternatively, the lack of massive clumps in the outer Galaxy could simply be due to statistics rather than any physics since there is a powerlaw mass function for clumps (CMF) and so a smaller population of clumps will have far fewer massive clumps, and none, if the clump population density is below some level (e.g., Snell et al 2002).…”
Section: Galactic Distribution Of Compact and Uc H II Regionsmentioning
confidence: 99%